Basal Vacuolization in Renal Tubular Epithelial Cells at Autopsy and Their Relation to Ketoacidosis. Issue 3 (30th January 2017) - Zhou, Chong; Yool, Andrea J.; Byard, Roger W.
Abstract: Basal vacuolization of renal tubular epithelial cells is a useful postmortem marker for ketoacidosis. To investigate its incidence and relationship to the severity of ketoacidosis, 158 autopsy cases with elevated β‐hydroxybutyrate (>1 mmol/L) over a 7‐year‐period were retrospectively reviewed. Sixty‐eight cases (43%) exhibited basal vacuolizations (vitreous β‐hydroxybutyrate: 1.16–29.35 mmol/L, mean 10.28 mmol/L), and 90 cases (57%) did not (vitreous β‐hydroxybutyrate: 1.03–13.7 mmol/L, mean 2.84 mmol/L). Quantitative analysis revealed on average a fourfold elevation in β‐hydroxybutyrate in cases with basal vacuolizations compared to those without; 10.3% of cases with β‐hydroxybutyrate concentrations between 1.01 and 2.00 mmol/L had basal vacuolizations, and this incidence increased to 33.3% with concentrations between 4.01 and 6.00 mmol/L. A marked increase in incidence to >70% was observed with concentrations >6.00 mmol/L, and basal vacuoles were invariably present (100%) with concentrations >14.01 mmol/L. This study demonstrates that basal vacuolizations are a sensitive marker for significant ketoacidosis and reaffirms its use as an indicator for likely cases of fatal ketoacidosis at autopsy.